Cross-Cultural Comparison (13 Countries) of Consumers’ Willingness to Eat Specific Insect Powders in Five Food Types - Suyeon Park; Edgar Chambers; Jeehyun Lee (Foods)
By 2050, the world’s population will rise to 9 billion, which implies that it is necessary to double protein production. We should consider more sustainable, alternative forms of protein. A solution to this is the use of insects, which offer high levels of protein and require less water than poultry, pork, and beef production. The objective of this study was to evaluate 13 countries’ consumer perceptions regarding the willingness to eat specific types of insects as powdered ingredients in five food types. An online survey was conducted using Check All That Apply (CATA) to assess consumer perceptions across 13 countries. Approximately 630 consumers in each country were surveyed (total n > 8100). The CATA data were analyzed using Cochran’s Q test, which showed highly significant differences among countries. The willingness to eat insects varied by country, food type, and insect species. The results of this study can be used to understand consumers’ perceptions of insects and offer an indicator that can be used when developing insect-containing foods in the future.